The Originality of Light and the Consequential Realization of Darkness based on Suhrawardi’s Perspective - Mahmoud Hedayat Afza; Abbass Sheikh Sho’aaii (حکمت اسرا, 2013)
In addition to the discussion of light, Suhrawardi has also made some statements about the realization of darkness in the outside world in some of his works. In the present paper, in addition to presenting Suhrawardi’s view of light and darkness, the illuminationist categorization of beings, the statements of Suhrawardi concerning the consequential realization of darkness, the background of his thought, an account of the different meanings of the concepts of “original” and “mentally posited”, the relationship between light and darkness based on Suhrawardi’s view, and the process of applying these two on the concepts of existence and essence will be analyzed. To this end, it has been clarified that what Suhrawardi means by light is a less general concept compared to what Mulla Sadra means by the term “existence” and this is why Suhrawardi has sometimes been accused, by Mulla Sadra and some of his commentators, of self-contradiction. However, by taking into account the concepts of existence and essence as utilized by Sheik Ahsaaii and applying them on the concepts of light and darkness, as put forth by Suhrawardi, one arrives at a novel interpretation of the “fundamental reality of existence” through which Suhrawardi’s philosophical school seems a bit more coherent and dynamic. Based on this latter interpretation, light or existence is considered to be “self-existent”, and darkness or essence “consequential being”, and not “accidental being”.